Models for studying coronary artery stenting - Alp, N; Ali, Z; Channon, K (2006)
Angioplasty and stenting are the most commonly performed revascularization procedures for symptomatic coronary artery disease. Stenting achieves immediate and stable arterial patency but induces a complex biological response in the vessel wall, which can lead to intimal hyperplasia and restenosis. The biophysical properties of stents have been investigated with computational and in vitro models, and the arterial response to stenting addressed using a range of in vivo models. This article reviews the strengths and limitations of these experimental systems, and their applicability to human coronary intervention. © 2006 Elsevier Ltd. All rights reserved.